General Economic Conditions and National Elections - Stigler, George J. (American Economic Review, 2016)
The fact that economic conditions influence voters is a leading commonplace of conversation in election years. The question is: Is this fact in fact a fact? Despite the overwhelming popularity of the fact, it has received neither an explicit theoretical analysis, presumably because it is so obvious that economic adversity should create political adversaries, nor until recently a satisfactory statistical analysis.' Gerald H. Kramer has presented a multivariate analysis of congressional elections which would strongly suggest that fluctuations in the rate of unemployment have no appreciable effect upon elections, but that fluctuations in per capita real income are influential. In the following pages I propose to (1) reaffirm his finding on the electoral unimportance of ordinary fluctuations in unemployment, (2) argue that, contrary to Kramer, fluctuations in real income also do not have important electoral effects, and (3) present an argument based upon rational voter behavior for the unimportance of general economic conditions in national elections.